2008
DOI: 10.1016/j.micinf.2008.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD8+T cells in the host response to Chlamydia

Abstract: Chlamydia infections constitute a major public health problem. Although multiple arms of the immune system participate in the control of Chlamydia in infected hosts, T lymphocytes are essential. This review focuses on the roles that CD8 + T cells may play in immunoprotection and immunopathology following recognition of Chlamydia-infected cells. KeywordsChlamydia; CD8 + T cells IntroductionMembers of the Chlamydiaceae family are obligate intracellular gram-negative bacteria that include the human pathogens Chla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 71 publications
1
18
0
Order By: Relevance
“…ϩ T cells are known to migrate to the infection site, and both human and mouse CD8 ϩ T cells have been shown to destroy cells that have been infected with Chlamydia (94). A recent study by Murthy and colleagues showed that wt and CD8 ϩ T knockout mice displayed similar clearances of C. muridarum following vaginal chlamydial challenge (95).…”
Section: T Cellsmentioning
confidence: 99%
“…ϩ T cells are known to migrate to the infection site, and both human and mouse CD8 ϩ T cells have been shown to destroy cells that have been infected with Chlamydia (94). A recent study by Murthy and colleagues showed that wt and CD8 ϩ T knockout mice displayed similar clearances of C. muridarum following vaginal chlamydial challenge (95).…”
Section: T Cellsmentioning
confidence: 99%
“…Studies of mice depleted of IFN-c implicate an important role in host defense to Chlamydia species in various mouse models as well (42). While multiple cell types produce IFN-c within the context of Chlamydia infection, including both CD4 + and CD8 + T cells, CD8 + T cells may serve as the most important source of this cytokine (63). For example, CD8 + T cells derived from wildtype mice, but not IFN-c-deficient mice protected naive mice from infection with C. trachomatis (64).…”
Section: Ifn-cmentioning
confidence: 99%
“…The findings of this study have important implications. (1) Previous reports suggest that certain CD8 + T cell clones that recognize specific chlamydial epitopes may assist in bacterial clearance (Wizel et al, 2008) and thus may be suitable as vaccine candidates. Our findings do not exclude this possibility; however, they suggest the need to exercise due diligence in applying such immune responses for the The number of normal oviducts or uterine horns (numerator) and the total number of oviducts or uterine horns evaluated (denominator) have been indicated in parentheses on the x-axis.…”
mentioning
confidence: 99%